Numerical modelling of sound intensity based on sound absorption coeficient of WCPP at 40% perforation ratio - Ula, Munirul (Penerbit UTM, 2007)
The boundary element method (BEM) is a numerical method that solves boundary value problems through the boundary integral equation (BIE) formulations. The applications of direct BIE formulations started in the early 1960 ‘s by Jaswon on a potential problem. This work was extended by Rizzo to solve the electrostatic problem. Since then, extensive research efforts have been made to develop BIE formulations for a variety of problems in applied mechanics. As the result, the BEM has become an attractive numerical tool useful in many engineering applications, such as acoustics, heat transfer, solid mechanics, structural mechanics, fluid mechanics, fracture mechanics, geomechanics, electromagnetic and so on.